(untitled) (Journal of actual problems of jurisprudence, 2019)
The article deals with the historical aspects of the banking system, institutional reforms of financial control and supervision. Briefly analyzes the development and establishment of law in the banking sector. Key words: banking, commercial banks, National Bank, legislation, monetary policy, deposits ipoteny contribution, the national currency (Tenge).